The Effect of Goat Milk Supplementation on Th1 and Th2 Responses of Peyer’s patch lymphocyte culture in dinitrochlorobenzene sensitized rat - Nurliyani, Nurliyani (2010)
Goat milk has been considered and recommended as an anti-allergy. However the information to support this practice has not been proven. Currently, prevention of allergy disease with avoiding the risk factor was direct to activate induction of immunologic tolerance. The objective of this research was to study the effect of goat milk and their fractions (casein and whey) supplementation on IFN-y (Th1 response)and IL-4 (Th2 response) in Peyer's patch (PP) lymphocyte culture supernatant and DTH (delayed-type hypersensitivity) response in DNCB (dinitrochlorobenzene)sensitized rat. Female Wistar rat 6-8 weeks old were devided into four grups of supplementation: 1) whey, 2) casein, 3) whole milk and 4) phosphate-buffered saline (PBS)/control. The dose of goat milk supplementation was 0.4 g/day with force feeding. The rats were sensitized on day 15 with DNCB at the dorsal area of the body, and challenged at their external ears on the day 24. The small intestinal PP were sampled at the day 14 (before DNCB sensitized) and the day 28 (after DNCB challenged. The ear tissues were sampled 72 hrsafter DNCB cahllenged. The content of IFN-y and IL-4 in PP lymphocyte culture supernatant were analized with ELISA (enzyme-linked immunosorbent assay) method, whereas the ear tissue were stained with haematoxylen-eosin. The results showed taht IFN-y and IL-4 in the after sensitized with DNCB were longer (P,0.05) than those before sensitized. Base on the histological figure, the rat that was supplemented with whey, showed no DTH reaction. In conclution, supplementation goat milk whey reduce the occurence of inflammatory reactions (Th1 response) and antibody-mediated allergic reactions (Th2 response) in DNCB sensitized Wistar rat. Therefore, the goat milk whey could be developed as an anti-allergy functional foods.